2013
DOI: 10.1016/j.sapharm.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Historical trend of disparity implications of Medicare MTM eligibility criteria

Abstract: Background Non-Hispanic Blacks (Blacks) and Hispanics have a lower likelihood of being eligible for medication therapy management (MTM) services than do non-Hispanic Whites (Whites) based on Medicare MTM eligibility criteria. Objective To determine whether MTM eligibility criteria would perform differently over time, this study examined the trend of MTM disparities from 1996–1997 to 2007–2008. Methods The study populations were Medicare beneficiaries from the Medical Expenditure Panel Survey. Proportions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…This study's findings concerning disparities follow patterns similar to those identified in prior research, as summarized in Table . It was previously reported that according to 2006 MTM eligibility thresholds (the most restrictive since MTM implementation), the adjusted odds ratios for meeting eligibility criteria for blacks and Hispanics compared to whites were 0.36–0.60 ( P <0.05) and 0.13–0.46 ( P <0.05) respectively .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study's findings concerning disparities follow patterns similar to those identified in prior research, as summarized in Table . It was previously reported that according to 2006 MTM eligibility thresholds (the most restrictive since MTM implementation), the adjusted odds ratios for meeting eligibility criteria for blacks and Hispanics compared to whites were 0.36–0.60 ( P <0.05) and 0.13–0.46 ( P <0.05) respectively .…”
Section: Discussionsupporting
confidence: 87%
“…To date, participation rates for MTM programmes have never exceeded 15% . Additionally, MTM eligibility criteria are implicated in racial and ethnic disparities in receiving MTM services . Non‐Hispanic blacks (blacks) and Hispanics may be less likely to meet MTM eligibility criteria because said criteria are predominantly based on prescription drug utilization, and these minorities typically use fewer prescription drugs and incur lower drug costs compared to their non‐Hispanic white (white) counterparts …”
Section: Introductionmentioning
confidence: 99%
“…11,12 However, previous research has reported that Blacks and Hispanics would be less likely to meet the Medicare eligibility criteria for MTM services. 9,13,14 For example, a study by Wang et al using historical data reported that the adjusted odds ratios for meeting MTM eligibility criteria for Blacks and Hispanics to Whites ranged from 0.36 to 0.60 ( P < .05) and 0.13 to 0.46 ( P < .05), respectively, according to 2006 eligibility criteria. 9 Similar results were found using the 2010 eligibility thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the same group of researchers suggested aligning MTM eligibility with a metric such as “potentially preventable future costs,” with the purpose of reducing spending and improving quality of care. 36 In January 2014, CMS proposed a new set of rules for Part D plans, acknowledging the limitations of the current MTM eligibility criteria including those reported by Wang et al 8,9,37 CMS proposed to expand MTM to all individuals who have at least two chronic conditions, have two Part D-covered drugs, and exceed a drug cost threshold of $620.40. Further research is needed to confirm that the proposed criteria will have the desired effects of increasing access to MTM services among Medicare beneficiaries and decreasing racial and ethnic disparities.…”
Section: Discussionmentioning
confidence: 99%
“…3 Wang et al has found that under the MTM eligibility criteria set forth in the MMA Non-Hispanic Blacks (Blacks) and Hispanics may be less likely to be eligible for MTM services than Non-Hispanic Whites (Whites) among the Medicare population according to current Medicare MTM eligibility criteria. 8,9 This is because the Medicare MTM eligibility criteria are predominantly based on medication utilization and costs, while Blacks and Hispanics tend to use fewer prescription medications and incur lower prescription medication costs. 3,10,11 Further, Wang et al found that existing Medicare MTM eligibility criteria may aggravate, rather than remediate, racial and ethnic disparities in health status.…”
Section: Introductionmentioning
confidence: 99%